Discovery of Evolutionary Loss of the Ubiquitin-like Autophagy-Related ATG12 System in a Lineage of Apicomplexa - Xiaoxia X. Lin; Yun D. Bai; Sichang T. Wang; Akira Nozawa; Tatsuya Sawasaki; Tatsunori Masatani; Kenji Hikosaka; Masahito Asada; Hirokazu Sakamoto (Cells)
The autophagy-related ubiquitin-like conjugation systems, the ATG8 and ATG12 systems, are universally conserved in eukaryotes. However, the covalent bond in the ATG12 system has recently been shown to be evolutionarily lost in Apicomplexa. Here, we show that all genes associated with the ATG12 system are absent in piroplasmida, a lineage within Apicomplexa. Comparative genomics of ATGs further shows that piroplasm ATG3 has lost the region necessary for ATG12 binding. However, our in vitro functional analysis using recombinant proteins demonstrated that ATG3 retained the ability to interact with ATG8 in Babesia bovis, a model species in piroplasmida. These findings provide evidence that the ATG8 system is functional, while the ATG12 system is completely lost in the common ancestor of piroplasmida and highlight the evolutionary flexibility of the ATG12 system in Apicomplexa.